Experimental trials of predicted CD4+ and CD8+ T-cell epitopes of respiratory syncytial virus - Qousain Naqvi, Syeda Tahira; Muhammad, Syed Aun; Guo, Jinlei; Zafar, Sidra; Ali, Amjad; Anderson, Larry J.; Rostad, Christina A.; Bai, Baogang (Frontiers in Immunology, 2024)
RSV is the most common cause of viral lower respiratory tract infections (LRTI) in young children around the world and an important cause of LRTI in the elderly. The available treatments and FDA-approved vaccines for RSV only lessen the severity of the infection and are recommended for infants and elderly people. We focused on developing a broad-spectrum vaccine that activates the immune system to directly combat RSV. The objective of this study is to identify CD4+ and CD8+ T-cell epitopes using an immunoinformatics approach to develop RSV vaccines. The efficacy of these peptides was validated through in vitro and in vivo studies involving healthy and diseased animal models. For each MHC class I and II, we found three epitopes of RSV proteins including F, G, and SH with an antigenic score of >0.5, and a projected SVM score of <5. Experimental validation of these peptides on female BALB/c mice was conducted before and after infection with the RSV A2 line 19f. We found that the 3RVMHCI (CD8+) epitope of the F protein showed significant results of white blood cells (19.72×103cells/μl), neutrophils (6.01×103 cells/μl), lymphocytes (12.98×103 cells/μl), IgG antibodies (36.9µg/ml), IFN-γ (86.96ng/L), and granzyme B (691.35pg/ml) compared to control at the second booster dose of 10µg. Similarly, 4RVMHCII (CD4+) of the F protein substantially induced white blood cells (27.08×103cells/μl), neutrophils (6.58×103cells/μl), lymphocytes (16.64×103cells/μl), IgG antibodies (46.13µg/ml), IFN-γ (96.45ng/L), and granzyme B (675.09pg/ml). In vitro studies showed that 4RVMHCII produced a significant level of antibodies in sera on day 45 comparable to mice infected with the virus. 4RVMHCII also induced high IFN-γ and IL-2 secretions on the 4th day of the challenge compared to the preinfectional stage. In conclusion, epitopes of the F protein showed considerable immune response and are suitable for further validation.